RECYCLING AND PYROLYSIS OF WASTE PLASTICS - Khatri , Amrita (International Journal of Research -GRANTHAALAYAH, 2015)
Plastic has achieved such an extensive market due to fact that it is lightweight, cheap, flexible and reusable. But now it is regarded as a serious hazard. All recommendation for and against plastics finally land up on the reality that plastics are slow to degrade. By the end of the 20th century, plastics are found as persistent polluters of many environmental niches, from Mount Everest to the bottom of the sea. There are numerous ways by which plastic pollution can be controlled. Pyrolysis is referred to as polymer cracking and its main advantages are that it can deal with plastic waste .This paper provides an overview of the science and technology of pyrolysis of waste plastics. The major advantage of the pyrolysis technology is its ability to handle unsorted, unwashed plastic. The production of gasoline, kerosene and diesel from waste plastics is an emerging technological solution to the vast amount of plastics that cannot be economically recovered by conventional mechanical recycling. The disposal and decomposition of plastics has been an issue which has caused a number of research works to be carried out in this regard. Currently, the paper reviews the production of Petroleum-based fuel viz. gasoline, kerosene and diesel from recycling of waste plastics is an emerging technological solution to the vast amount of plastic wastes that cannot be economically recovered by conventional mechanical recycling operations. This involves the use of pyrolysis which permits recovery of valuable gasoline and diesel-range hydrocarbons from waste plastics that are otherwise land filled.